Pot do zmage v ženski športni gimnastiki - fair play med nadarjenostjo in tveganjem - Zurc, Joca (Šport (Ljubljana), 2018)
Women's artistic gymnastics is one of the most attractive Olympic sports and is marked by an early age training, top achievements in sport career during the adolescence and short competitive period. In our study we were interested, what is the way to success in women's artistic gymnastics from the perspective of the elite athletes. Phenomenological study with a semi-structured and in-depth interviews was conducted on a sample of 37 female gymnasts. Qualitative content analysis was used to find the main themes in the statements of interviewees. The findings showed a four stage process for creating an elite achievements: 1) enrolling in gymnastic training, 2) process of training, 3) participation at competitions, and 4) end of the sport career as the elite athlete. With a purpose to develop a child's gymnastic potential up to the possible maximum with the consideration of athlet's rights, developmental needs and health it is necessarily to dedicate an adequate attention to the following factors: comprehensive talent selection, gradual escalation of complexity, raising the age limit for the senior competitions, adequate rehabilitation of health issues, and early ending of sports career overcome.
Keywords: etika maksimuma; fenomenološka študija; nadarjenost; Olimpijske igre mladih; športna gimnastika; ženske